2020
DOI: 10.21203/rs.3.rs-72121/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The T helper (Th) T Cytotoxic (Tc) Ratio in Hemophilia Disease

Abstract: Background and Objectives:In this study, we investigated the T helper (Th) to T cytotoxic (Tc) ratio in children suffered from hemophilia disease. 80 diagnostic subjects referred to Ali Asghar hospital of Zahedan city, Zahedan-Iran, were selected and the ratio of these cells were analyzed by analytic descriptive methods.Method of study:Two mls of EDTA anti coagulated whole blood was collected. Immunophenotyping of lymphocytes count was carried out by FACS analysis using a double CD4 and CD8 kit. The mean ± SD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…A study by Zahiri et al (11) reported that 45.9%, 40.9%, and 70.4% of nurses experience high levels of emotional exhaustion, depersonalization, and personal inefficacy. Another study showed that nurses reported low, moderate, and high levels of emotional exhaustion, depersonalization, and personal inefficacy, respectively (18).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Zahiri et al (11) reported that 45.9%, 40.9%, and 70.4% of nurses experience high levels of emotional exhaustion, depersonalization, and personal inefficacy. Another study showed that nurses reported low, moderate, and high levels of emotional exhaustion, depersonalization, and personal inefficacy, respectively (18).…”
Section: Discussionmentioning
confidence: 99%
“…This increase is attributed to the fact that the prolonged Covid-19 detection and the time required to perform x-rays and related tests have increased the waiting time of clients for physician visit. The increase in the ED visits and the waiting time are among the risk factors for discharge against medical advice (34). Wilber et al showed a higher DAMA when the utilization rate of an emergency department exceeds its capacity.…”
Section: Discussionmentioning
confidence: 99%